Meias de gorgurão como monoterapia no tratamento do linfedema de membros inferiores - Guimarães, Tânia Dias (2014)
Introduction: With difficulties to associate different therapies, a compression mechanism is the best choice of monotherapy in the treatment of lymphedema. Objective: The aim of the current study was to assess over one month the effectiveness of a compression mechanism as monotherapy to reduce the volume of leg lymphedema using a cotton-polyester (grosgrain) stocking.Patients and Method: In 2013, 26 consecutive patients with one-sided or bilateral lower leg lymphedema were assessed in a prospective clinical trial in the Clinica Godoy, Sao Jose do Rio Preto, Brazil. Six participants were male and 20 were female with ages ranging from 26 to 72 years (mean: 49 years). All patients with clinical diagnosis of grade II lower leg lymphedema regardless of the cause were included. Patients with a history of allergies, intolerance of compression mechanisms and those with infections, joint immobility and other conditions that might interfere with edema were excluded. All patients were evaluated by volumetry using the water displacement technique, at the beginning of treatment and weekly thereafter. The mechanism of compression was explained to all participants and they were advised about the need of frequent adjustments, how to adjust the stockings and the necessary care. At each consultation, volumetric variations, the patient’s tolerance to treatment, adverse events, correct usage and the need for adjustments were assessed. Major adjustments were made by a seamstress after evaluation by the treatment team. The data was input on a Microsoft Excel spreadsheet. The study was approved by the Research Ethics Committee and all patients signed informed consent forms. Quantitative variables are reported as means and standard deviation when the distribution was normal or medians and interquartile range when the data was asymmetric. The relationships of these variables in respect to the outcomes were compared using the Wilcoxon test with an alpha error of 5% being considered acceptable. Results: Forty-nine legs of the 26 participants with lymphedema were assessed. From week to week, both positive and negative variations were detected during the treatment using grosgrain stockings. In the first week, fifteen (30.61%) limbs increased in volume and 34 (69.38%) reduced in size. In the second week, five (10.20%) continued to increase and 44 (89.79%) reduced; in the third week four (8.16%) had further increases and 45 (91.83%) reduced and in the fourth week only three limbs (6.12%) continued to increase and 46 (93.87%) reduced in size. As a total, the reductions were statistically significant (p-value < 0.001) in all evaluations when the baseline is compared with the other weeks, the first week with the others and the second week with the others, but there was no significant difference between the third and fourth weeks (p-value = 0.07). Conclusion: The grosgrain stocking as monotherapy is effective in reducing swelling in the treatment of grade II lower leg lymphedema. Patients should receive guidance and be trained in respect to the correct usage of compression stockings.